TRANSFORMATIONS OF IDENTITY AND SUBJECTIVITY IN SYMBOLIC PRACTICES OF RESISTANCE UNDER CONDITIONS OF WAR: A PHILOSOPHICAL AND PSYCHOLOGICAL INTERPRETATION OF THE INTERNAL FAMILY SYSTEMS MODEL - Lukashenko, Maryna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines the problem of identity and subjectivity under conditions of war through the conceptual framework of the Internal Family Systems (IFS) model. Particular attention is paid to the transformation of subjectivity under conditions of existential threat and symbolic violence, as well as to practices of resistance as mechanisms of psychological regulation and cultural resilience. The aim and tasks. The aim of the article is to provide a philosophical and psychological analysis of transformations of identity and subjectivity within symbolic practices of resistance under conditions of war through the lens of the IFS model. The tasks include analyzing the theoretical potential of the IFS model for interpreting traumatic experience and Self-leadership, examining symbolic practices of resistance as mechanisms supporting individual and collective subjectivity, and conceptualizing “unburdening” as a process of releasing traumatic meanings at personal and cultural levels. Research methods. The methodological framework combines phenomenological analysis, critical social philosophy, and systemic psychotherapy approaches. Practices of resistance are interpreted as symbolic and psychological processes of unburdening associated with the release of burdensome beliefs, emotions, and traumatic meanings that no longer correspond to changing reality. Research results. The study demonstrates that symbolic practices of resistance (linguistic, ritual, and visual) function not only as forms of social expression but also as mechanisms of collective processing of traumatic experience and preservation of collective subjectivity. The analysis shows that the IFS model provides a productive interpretive framework for understanding processes of self-regulation, differentiation, and integration under conditions of war and collective trauma. Discussion. The article conceptualizes the notion of “symbolic unburdening of culture” as a philosophical interpretation of resistance practices aimed at separating collective identity from imposed traumatic meanings. The analysis draws on Agamben’s concept of “bare life,” Butler’s understanding of vulnerability and grievability, and Habermas’s concept of post-conventional identity to interpret symbolic resistance as a process of re-subjectification. Conclusions. The proposed philosophical and psychological perspective expands contemporary interpretations of subjectivity, resilience, and identity transformation under conditions of war and collective trauma. The integration of phenomenological reflection with systemic psychotherapy approaches creates a conceptual basis for further interdisciplinary studies of identity and collective resilience